Self- And Peer-Reflection in Teaching Practice Program: Unveiling Reflection Preference, Benefits, and Challenges - Luh Gede Eka Wahyuni (Indonesian Postgraduate Foreign Language Education Association, 2025)
Previous studies have been conducted to explore the incorporation of self-reflection and peer-reflection in both quantitative and qualitative works, yet the delve of the reflection preference as well as the benefits and challenges of its employment remained indefinitely. This study, employed in a survey form, was conducted in a state university involving 107 sophomore students who were taking Microteaching Course. Questionnaire and in-depth interview were administered to collect the data. The data from the questionnaires were analyzed to reveal the descriptive tendency of their perception, while the interview results were interpreted through content analysis. The findings highlighted that 7 (6.5%) students preferred to employ self-reflection, 21 people (19.6%) desired to use peer-reflection, and 79 (73.9%) preferred to have both in their teaching reflective practice. Specifically, among those 21 students, 16 (76.2%) out of them preferred to have their lecturers as the source of the feedback, while the rest was confident enough to be reflected by the other students. Furthermore, the results also revealed that the incorporation of self- and peer-reflection benefitted them in enhancing their ability of lifelong learning, self-assess, self-belief, and self-metacognition and awareness development. However, they also encountered some challenges during the reflection employment such as assessment objectivity bias, less confidence in delivering the feedback, time limitation, and diverse perceptions and interpretations. To overcome the issues, a comprehensive approach is needed to explore appropriate strategies to mitigate the identified issues as well as to conduct a longer-term study investigating the impacts on teaching competence and professional development.